Safety First, Performance Next: Exploring the Interplay between Perceived Safety Climate and Employee Performance - Birowo, Yohanes Arga Poetra; Putra, Tegar Satya (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2023)
This study probes the influence of a perceived safety climate on task and contextual performance. Using the Job Demand Resource model, it's hypothesized that a pronounced safety climate counterbalances high job demands. A questionnaire, grounded in established instruments of safety climate and employee performance, was administered to 46 construction workers. SEM-PLS analysis of this purposive sample highlighted that a perceived safety climate significantly elevates both performance facets. Such results mirror past studies, positing that safety-centric environments not only amplify task outputs but also inspire proactive organizational behaviors. Despite its insights, the study's reliance on self-reported data and its sampling approach pose limitations, hinting at future research directions. From a managerial standpoint, this underscores the pivotal role of a robust safety culture, not just in risk deterrence but also as an anchor for optimal employee output.